Alloy Engineering: Controlling Nanoscale Thermal Expansion of Monolayer Transition Metal Dichalcogenides by Alloy Engineering (Small 3/2020). Issue 3 (23rd January 2020) - Hu, Xuan; Hemmat, Zahra; Majidi, Leily; Cavin, John; Mishra, Rohan; Salehi‐Khojin, Amin; Ogut, Serdar; Klie, Robert F.
Abstract : In article number 1905892, Robert F. Klie and co‐workers show that alloy engineering can be used to control the thermal expansion (TEC) of 2D materials, including the transition metal dichalcogenide Mo1− x W x S2 . Using a combination of atomic‐resolution scanning transmission electron microscopy imaging and electron spectroscopy at elevated temperature with first‐principles modeling, the dependence of the TEC on the chemical composition of Mo1− x W x S2 is demonstrated. Image credit: John Cavin, Washington University in St. Louis.